INHIBITION OF LIPID PEROXIDATION AND MICROBIOLOGICAL IMPROVEMENT OF BROILER THIGH QUALITY AND CHARACTERISTICS BY ADDING CYPERUS ROTUNDUS POWDER AND VITAMIN E TO CHICKEN FEED - A. A. Al-Azzami; Th. T. Mohammed; S. M. Farhan (مجلة الأنبار للعلوم الزراعية)
Different amounts of Cyperus rotundus tuber powder and vitamin E were added to broiler feed during the breeding period to investigate their effects on the thigh meat cuts of the chicken carcasses. The findings show that adding the powder in 2.5, 5, and 7.5 g/kg feed maintained the pH stability of the thigh meat as well as significantly enhanced its water-retention ability. The findings also showed that all the different concentrations of the additives prevented fat from oxidizing in the chicken thigh meat. This was evidenced by the significantly lower MDA, PV, and FFA levels (P<0.05) compared to the control treatment without the additives. The treatments that prevented lipid oxidation the most were the 5 and 7.5 g/kg feeds. Also, the thigh meat from the 7.5 g/kg treatment had better taste and microbial characteristics over the 5 g/kg treatment while those receiving the 2.5 g/kg vitamin E or the control treatment did not show any significant effects. The results also showed that chicken thigh meat in the 5 and 7 g/kg C. rotundus tuber powder treatment was better in terms of taste, juiciness, and overall acceptance. Finally, adding the powder stopped the production of free radicals and free fatty acids in the chicken thigh meat, which meant that the fat oxidation markers declined.